Community Structure, Biodiversity and Spatiotemporal Distribution of the Black Flies (Diptera: Simuliidae) Using Malaise Traps on the Highest Mountain in Thailand - Wichai Srisuka; Chayanit Sulin; Kittipat Aupalee; Thapanat Phankaen; Kritsana Taai; Sorawat Thongsahuan; Atiporn Saeung; Hiroyuki Takaoka (Insects, 2021)
Black flies form a group of small blood-sucking insects of medical and veterinary importance. This study aimed to investigate the community structure, biodiversity and spatial and temporal distribution of adult black flies in tropical rain forests, by using malaise traps in Doi Inthanon National Park, northern Thailand. Malaise traps were placed along six elevational gradients (400 m to 2500 m, above sea level) at Doi Inthanon National Park, Chiang Mai province, from December 2013 to November 2014. A total of 9406 adult female black flies belonging to five subgenera—Daviesellum (2%), Gomphostilbia (23%), Montisimulium (11%), Nevermannia (16%) and Simulium (48%)—were collected. Among 44 taxa found, S. tenebrosum complex had the highest relative abundance (11.1%), followed by the S. asakoae species-group (9.6%), the S. striatum species-group (7.7%), S. inthanonense (6.6%), S. doipuiense complex (6.4%), S. chomthongense complex (5.3%), S. chumpornense (5.1%) and S. nigrogilvum (4.1%). Two human-biting species—S. nigrogilvum and species in the S. asakoae species-group—were found in all of the collection sites with 100% species occurrence. Species richness was highest at mid elevation (1400 m), which is represented by 19 black fly species. The peak and lowest seasonal abundance was observed in the rainy and hot season, respectively. Seasonal species richness was highest in the cold season, except for that from elevation sites at 700 m, 1700 m and 2500 m. This study revealed that the malaise trap is effective in providing important data for further monitoring of the effects of environmental changes and conservation planning on the biodiversity of black flies in Doi Inthanon National Park.